Obstacles and Solution to PPkn Online Learning at SMK Negeri 3 Salatiga - Gian Hanjani; Nani Mediatati (Jurnal Mantik, 2022)
The purpose of this study is to describe the obstacles in PPKn (Pancasila and civic education) online learning and solutions to overcome them at SMK Negeri 3 Salatiga. This research is a qualitative descriptive study. Data collection techniques using interviews, observations, and questionnaires. Respondents consisted of 3 PPKn teachers and 30 students of class X. The results showed that there are obstacles experienced by teachers and students. The obstacles faced by PPKn teachers were related to 1) character education/moral values ??of students, 2) slow learning applications/errors, 3) student discipline, and 4) selection of learning methods. Constraints faced by students are related to 1) student enthusiasm for learning, 2) difficult material to understand, 3) device constraints, 4) internet quota, and 5) limited communication between students. These obstacles have been made efforts and solutions by teachers and schools, but renewal and innovation need to be done to improve better learning.